No GIST-type c-kit gain of function mutations in neuroblastic tumours. Issue 7 (23rd June 2005) - Korja, M; Finne, J; Salmi, T T; Haapasalo, H; Tanner, M; Isola, J
Abstract : Aims: Neuroblastic tumours (NTs) have been shown to respond to imatinib treatment in vivo and in vitro, possibly via inactivating the c-kit receptor. The purpose of this study was to identify gastrointestinal stromal tumour (GIST)-type c-kit gene associated mutations in exons 9, 11, 13, and 17 in NTs to recognise a subset of tumours that would probably respond to imatinib treatment. Methods: Expression of the c-kit protein was detected immunohistochemically in a total of 37 archival paraffin wax embedded NTs using polyclonal rabbit antihuman c-kit antibody. After immunohistochemistry, c-kit gene associated chromosomal mutations in all cases of NT were detected with denaturing high performance liquid chromatography (HPLC). Results: Denaturing HLPC analysis did not reveal GIST-type mutations in four immunohistochemically detected c-kit positive or in 33 c-kit negative NTs. Conclusions: c-kit receptor expression and GIST-type c-kit gene mutations are rare events in NTs. Oncogenic activation of c-kit in NTs presumably differs from that of GISTs, which may influence their responsiveness to imatinib treatment. Whether c-kit has an essential role in the pathogenesis of NTs remains to be investigated.